Kasus Kasus Kontemporer: Bank Syariah, Asuransi Dan Pasar Modal - Winarsih, Tri; Purnomo, Muhammad Iksan (ASAS, 2021)
Today's financial institutions have been formed in various ways, have become various models that have never been formed before and are formed today. This is a form of response to all kinds of phenomena in society with all kinds of needs. Each institution is formed with its own purpose and role, these financial institutions complement each other's human economic activities. Contemporary financial institutions that will be discussed in this study are Islamic Banks, Insurance and Capital Markets. This research is included in the literature review which will examine the understanding and several other important things about the three contemporary institutions, based on primary data sources in the form of laws and secondary data sources originating from various literature on financial institutions. The results of this research will explain the meaning of the three contemporary institutions based on the applicable laws and regulations in Indonesia, accompanied by explanations based on the understanding of economists in various literatures, besides that it will also explain the legal basis, basic principles and actors of the three contemporary institutions.Keywords: Contemporary financial institutions, Islamic Banking, Insurance, Capital Markets.